Content Validity of Three-Tier Multiple Choice Virtual Reality-Based Assessment with Embedded Ethno-SSI Concepts on Acid-Base Topics - Zamira Zia'ul Huda; Sri Yamtinah; Ari Syahidul Shidiq (Online Learning In Educational Research (OLER), 2025)
Research on acid-base misconceptions at the high school level is extensive, but studies at the university level remain limited. Due to the prevalence of these misconceptions, developing accurate instruments for early detection is crucial. This study developed a three-tier multiple-choice virtual reality-based assessment integrating the ETHNO-SSI concept for acid-base topics. The study employed the Borg and Gall R and D model to evaluate content validity.The study used a developmental design, with face validation by six expert reviewers using a rubric to evaluate content validity, construct relevance, clarity and contextual integration. Processing of the data involved the use of Aiken’s V index. The results also evidenced a high content validity for all the dimensions studied, indicating that the instrument is pedagogically sound and culturally relevant. By embedding Ethno-SSI in immersive VR platforms, this assessment approaches represents a new path in the pursuit of students’ conceptual challenges when dealing with sociocultural decision making in real-world conditions. This study provides valuable information to the development of multidimensional chemical assessment instruments to link sociocultural innovation, recover notions of acid-base misconceptions, and incorporate cultural relevance in chemistry education.